Mapping of Physicochemical Properties of Well and River Water in Sayang and Cikeruh Villages, Sumedang Regency - Arisandy, Maharani; Fitriani, Dini; Agustine, Eleonora; Kirana, Kartika Hajar; Atthailah, Luthfi Tanton; Fidela, Shafa Maura; Pamula, Alden Rizqi; Fajar, Raya Putra Sang (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
Water is an essential resource for human life, yet its quality has declined due to population growth and land-use changes. Sayang and Cikeruh Villages in Jatinangor District have experienced environmental pressures from land conversion and domestic activities that may affect groundwater and surface water quality. This study aims to map and analyze the physicochemical parameters of water, including temperature, pH, electrical conductivity (EC), and total dissolved solids (TDS), in well water and the Cikeruh River. Measurements were conducted at ten well and nine river sampling points and analyzed using descriptive, spatial, and multivariate methods. The results show that most well water samples meet clean water quality criteria; however, several locations exhibit elevated EC and TDS values and slightly acidic pH, indicating the influence of surrounding residential activities. In contrast, river water quality remains within acceptable limits for all measured parameters. Multivariate analysis reveals a strong correlation between EC and TDS in both well and river water, indicating their importance as key indicators of water quality. Spatial analysis shows that water quality in the southern part of the study area tends to be lower than in the northern part. Continuous monitoring and appropriate water resource management are therefore necessary to maintain water quality in the study area.